1988
DOI: 10.1073/pnas.85.3.900
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition and fluidity of the human immunodeficiency virus.

Abstract: 900The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C. §1734 solely to indicate this fact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(116 citation statements)
references
References 40 publications
6
110
0
Order By: Relevance
“…These differences in hydration also affect lateral packing of the lipid bilayers, another primary factor that governs the interaction and fusion between membranes (Yang et al, 1997). It has been reported that the infectivity of the RNA viruses (such as HIV and Sendai virus) is reduced with the reduction of the cholesterol content in the viral envelope (Citovsky et al, 1986;Aloria et al, 1988), which indirectly supports this speculation. Among the three different virosome types, the ASVE-virosomes exhibited the best gene-transfer Fig.…”
Section: In Vitro Gene Transfer Mediated By F/hn-virosomes Of Varied supporting
confidence: 64%
“…These differences in hydration also affect lateral packing of the lipid bilayers, another primary factor that governs the interaction and fusion between membranes (Yang et al, 1997). It has been reported that the infectivity of the RNA viruses (such as HIV and Sendai virus) is reduced with the reduction of the cholesterol content in the viral envelope (Citovsky et al, 1986;Aloria et al, 1988), which indirectly supports this speculation. Among the three different virosome types, the ASVE-virosomes exhibited the best gene-transfer Fig.…”
Section: In Vitro Gene Transfer Mediated By F/hn-virosomes Of Varied supporting
confidence: 64%
“…Crucially, the viral membrane is known to be enriched in sphingolipids and cholesterol relative to the plasma membrane (Aloia et al, 1988(Aloia et al, , 1993. There is therefore a significant weight of evidence supporting a role for lipid rafts in the assembly of HIV.…”
Section: Retrovirusesmentioning
confidence: 99%
“…Furthermore, the triacylglycerols apparently influence membrane fluidity and permeability, parameters which increase with elevated lipid/protein ratio (Aloia et al, 1988). Membrane permeability to certain chemical agents, including anti-cancer drugs and anaesthetics, is impaired by triacylglycerols.…”
Section: Discussionmentioning
confidence: 99%